2015
DOI: 10.1039/c5nr02498f
|View full text |Cite
|
Sign up to set email alerts
|

MoS2 ultrathin nanosheets obtained under a high magnetic field for lithium storage with stable and high capacity

Abstract: A new strategy, namely a high magnetic field-induced method, has been designed to enhance lithium storage properties of MoS2 ultrathin nanosheets. The MoS2 ultrathin nanosheets obtained under 8 T exhibit improved cycling stability at high currents, better rate performance and reduced electrochemical impedance, compared to MoS2 ultrathin nanosheets obtained without a high magnetic field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…MoS 2 nanosheets, which were exfoliated from its bulk counterpart or synthesized in a number of different ways, exhibited better electrochemical performances compared with MoS 2 bulk . Hu et al reported that a high magnetic field (8 T) was used to control the synthesis of MoS 2 ultrathin nanosheets, and the products have fewer defects and better crystallite orientation. High‐pressure hydrothermal method was adapted to synthesize hierarchical MoS 2 spheres composed of ultrathin nanosheets.…”
Section: Introductionmentioning
confidence: 99%
“…MoS 2 nanosheets, which were exfoliated from its bulk counterpart or synthesized in a number of different ways, exhibited better electrochemical performances compared with MoS 2 bulk . Hu et al reported that a high magnetic field (8 T) was used to control the synthesis of MoS 2 ultrathin nanosheets, and the products have fewer defects and better crystallite orientation. High‐pressure hydrothermal method was adapted to synthesize hierarchical MoS 2 spheres composed of ultrathin nanosheets.…”
Section: Introductionmentioning
confidence: 99%
“…The literature data are separated into exfoliation of MoS 2 and hydrothermally synthetic MoS 2 electrodes. The filled black pentagrams represent our capacity data, normalized to the total anode mass: a) cycle performances of MoS 2 nanosheets with maximum cycle number; b) rate capacities of MoS 2 nanosheets …”
Section: Resultsmentioning
confidence: 99%
“…Thes ize of MoS 2 nanosheetsw as smaller than that of commonM oS 2 nanosheets and 2H polytype was more stable;t hus,t hese nanosheets were appropriate as anode materials for LIBs.E lectrochemical studies showed that the MoS 2 nanosheets possessed ah igh reversible capacity of 1133 mAh g À1 after 130 cycles,ahigh rate capability (817.1 mAh g À1 at 2000 mA g À1 ), and aC oulombic efficiency of over 97 %a fter three cycles.I nt erms of the useo fa ne nvironmentally friendly,c ost-effective,s calable,a nd facile liquid exfoliation route with pristine MoS 2 powders as starting materials,w e believet hat the achieved electrochemical performance, which is comparable to most available data reported in the literature,i sfascinating for LIBs. The filled blackp entagramsrepresentour capacityd ata, normalized to the total anodem ass:a )cycle performances of MoS 2 nanosheetsw ith maximumcyclenumber; [9,[11][12][13][14][15][16][17][18][19] b) rate capacities of MoS 2 nanosheets. [9, 11-21, 23, 42] Energy Technol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31] Also, the MFEs on the growth of materials have been extensively studied by our group, which found that both the structure and the properties of materials can be regulated by magnetic elds. [32][33][34][35][36][37][38] For example, it is believed that during Co 3 O 4 growth, the alignment of the spins and thus the magnetic and crystal lattices of Co 3 O 4 are inuenced by the external magnetic eld. 35 In this paper, we extend the study to grow single crystals of formate-based perovskites [(CH 3 ) 2 NH 2 ][Mn(HCOO) 3 ] (DMMnF) under a high magnetic eld.…”
mentioning
confidence: 99%